2t^2 + 10t - 48 = 0
(2t - 6)(t + 8) = 0
(2t - 6) = 0 or (t + 8) = 0
2t = 6, so t = 3 or t = -8
t = 3 or -8
2007-01-02 11:43:57
·
answer #1
·
answered by Tom :: Athier than Thou 6
·
1⤊
0⤋
First: find a number divisible by the coefficients which is 2 > Factor out 2 and multiply it by the remaining terms to get 2t^2 + 10t - 48 >
2(t^2 + 5t - 24) = 0
Sec: factor the terms in the parenthesis:
2(t + 8)(t - 3) = 0
Third: solve for "t" > take both sets of parenthesis and equal them to "0" >
t + 8 = 0
t + 8 - 8 = 0 - 8
t = - 8
t - 3 = 0
t - 3 + 3 = 0 + 3
t = 3
t = -3 and 8
2007-01-02 12:31:25
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
2t^2+10t-48=2(t^2+5t-24)
=2(t+8)(t-3)
=0.
By the zero product property, the product of two real numbers is zero if and only if at least one of the two numbers is zero: ab=0 -> a=0 or b=0.
So,
t+8=0 ->t=-8 or t-3=0 ->t=3.
Thus, t=-8 or t=3.
It is very important to remember that the zero product property is only valid for products involving zero. _Never_ apply it to a product involving a number involving a number other than zero.
Good luck!
2007-01-02 11:44:05
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
2t^2+10t-48=0 divide by 2
t^2+5t-24=0
(t-3)(t+8)=0
t-3=0
t=3
t+8=0
t=-8
t=3, -8
2007-01-02 11:41:06
·
answer #4
·
answered by yupchagee 7
·
1⤊
0⤋
2t^2+10t-48=0
2(t^2+5t-24)=0
2[(t-3)(t+8)]=0
So, t-3 or t+8 = 0
t-3 = 0
t=3
t+8 = 0
t=-8
So, t=3 or -8
2007-01-02 11:56:41
·
answer #5
·
answered by danjlil_43515 4
·
1⤊
0⤋
(2t-6)(t+8)
2(t-3)(t+8)
t=3 or -8
2007-01-02 11:40:01
·
answer #6
·
answered by raj 7
·
1⤊
0⤋
2t^2+10t-48=0
4t+10t-48=0
14t-48=0
14t=-48
t= -3.43
2007-01-02 11:38:32
·
answer #7
·
answered by AYBZ 2
·
0⤊
2⤋
(2t+16)(t-3)=0
2t+16=0
2t=-16
t=-8,3
2007-01-02 11:41:44
·
answer #8
·
answered by Dave aka Spider Monkey 7
·
1⤊
0⤋